McMummy - Betsy Byars (U.S.A Puffin Book, 1993)
While taking care of the greenhouse during Professor Orloff's absence, Mozie encounters a humming, mummy-shaped, human-sized pod among the creepy oversized vegetables. By the author of Summer of the Swans.
Keywords: Science Fiction -- Science Fiction